Application of Iterative Updating Geological Modeling Method in Geological Guidance of Shale Oil Horizontal Wells - LI Zhihong; LEI Qihong; WU Yingzhang; HE Youan; CHENG Hao; WANG Bo; ZHOU Jingping; ZHAO Yi (Cejing jishu)
In the Ordos basin Longdong area, the Chang 7 memeber of Yanchang formation is a typical interbedded shale oil reservoir with thin single oil layer, fast lateral and vertical changes, and strong heterogeneity. Currently, the prediction of inter well oil layer distribution characteristics is mainly based on two-dimensional geological sections and oil layer maps, which has low precision and leads to difficulties in geological guidance for horizontal wells, restricting the improvement of oil layer encounter rate. In order to further improve the oil layer encounter rate of shale oil horizontal wells, the method combines geological, logging, well-logging and 3D seismic data to select the optimal well-seismic integration modeling method, establishes a fine structural model, rock facies model and attribute model, and quantitatively represents the spatial distribution characteristics of shale oil drilling platform geological sweet spots in three-dimensional space. The gamma curve is optimized to establish a horizontal well geological guidance model, and the iterative geological modeling method is used to update the three-dimensional geological structure model and geological guidance model using the real-time logging and drilling data of the horizontal well, further improving the oil layer prediction accuracy and accurately predicting the distribution of drillhead front geological sweet spots in the horizontal well, guiding the efficient drilling of the horizontal well. Using this method, the geological guidance of HHX platform HHX-1 well is guided, and the measured oil layer encounter rate is 93.4% after drilling, which is significantly higher than the oil layer encounter rate of the adjacent well on the same platform. This shows that the iterative updating of geological modeling method can help improve the oil layer encounter rate of shale oil horizontal wells and has important guidance significance for the later stage geological guidance of Longdong shale oil.